2013
DOI: 10.1038/sc.2013.103
|View full text |Cite
|
Sign up to set email alerts
|

Dissociations in the meaning of risk between health-care professionals and individuals with spinal cord injury

Abstract: Objective: Risks have been a central concern in stem cell research overall, and in clinical trials of individuals with spinal cord injury (ISCIs) in particular. We sought to elucidate how two important stakeholder groups-health-care professionals (HCPs) and ISCIs-view and value both the physical and non-physical risks of stem cell interventions. Setting: The study was conducted in Canada, and included participants from both Canada and the United States America. Study design: We used semi-structured interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…21,22 The focus on the goal of seizure freedom could improve by incorporating the values of parents, who emphasize the importance of quality of life and a holistic risk-benefit trade-off on treatment, as supported in other decision-making and outcome literature. 8,19,23,24 In addition, as parents may have early preferences for the latest neurotechnologies, physicians identified the role of careful communication and guidance toward the most appropriate treatment. Communication style-for example, timing and responsiveness-is important to decision making for resective epilepsy surgery 19 and other pediatric chronic disease 25 and is critical for informed consent.…”
Section: Implications Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 The focus on the goal of seizure freedom could improve by incorporating the values of parents, who emphasize the importance of quality of life and a holistic risk-benefit trade-off on treatment, as supported in other decision-making and outcome literature. 8,19,23,24 In addition, as parents may have early preferences for the latest neurotechnologies, physicians identified the role of careful communication and guidance toward the most appropriate treatment. Communication style-for example, timing and responsiveness-is important to decision making for resective epilepsy surgery 19 and other pediatric chronic disease 25 and is critical for informed consent.…”
Section: Implications Of This Studymentioning
confidence: 99%
“…6 For various areas of biomedicine, neuroethics has been used as a lens from which to understand the decision-making values, priorities, needs, and other key factors relevant to diverse stakeholders. For example, in a series of qualitative studies on stem cells, areas of misalignment were identified between individuals with spinal cord injuries and health care providers in the target timing of clinical trials, 7 definitions of risk, 8 and trust. 9 In the realm of novel neurotechnology, results of a first-in-human brain-computer interface trial on adults with epilepsy revealed a complicated tension between the transformative sense of autonomy afforded by the device and feelings of self-estrangement.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, numerous studies have shown that researchers and participants have divergent expectations and risk tolerance with regard to SCI research outcomes [11,12] and diverse functional priorities for BCI use [13]. Given these differences between participants, clinicians, and researchers regarding the purpose of such research, special protocols may be needed to ensure that expectations are discussed and disagreement is fairly adjudicated.…”
Section: When the Research Participant Becomes A Co‐investigatormentioning
confidence: 99%
“…Using methods from past studies, we applied a thematic analysis approach to the data, involving a rigorous and an iterative process in which portions of raw data are labelled and examined for broader themes across the data set. 10 To develop the initial coding frame, two coders who were trained in qualitative research methods acted independently to examine the transcripts and came together to compare codes until a consensus was reached. These codes were continuously revisited, revised and added to as analysis went on.…”
Section: Discussionmentioning
confidence: 99%
“…Trust and effective and trusted communication in the patient-physician relationship have been linked to positive patient behaviours involving treatment decisions, compliance and information disclosure. 5 In the present study, one of a series on readiness for clinical trials, 6 decision making, 7 expectation of benefit and risk, 8 advocacy 9 and risk, 10 we sought to examine how these trusting relationships specifically are fostered and threatened in the context of the conversation about stem cell interventions for SCI.…”
Section: Introductionmentioning
confidence: 99%